2018
DOI: 10.3348/kjr.2018.19.4.568
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Performance of Liver MRI without Intravenous Contrast for Detecting Hepatocellular Carcinoma: A Case-Controlled Feasibility Study

Abstract: ObjectiveTo preliminarily evaluate the diagnostic performance of an unenhanced MRI for detecting hepatocellular carcinoma (HCC) with a case-control study design.Materials and MethodsThe case group consisted of 175 patients with initially-diagnosed HCC, who underwent a 3T liver MRI. A total of 237 HCCs were identified. The number of HCCs that were smaller than 1 cm, 1 cm ≤ and < 2 cm, and ≥ 2 cm were 19, 105, and 113, respectively. For the control group, 72 patients with chronic liver disease, who did not have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
2
38
3
3
Order By: Relevance
“…and 76.4-87.5%, respectively. 21,23 For EOB-AMRI, the sensitivity and specificity ranged from 80.6-83.7% and 90.6-91.6%, respectively. 19,22 Although these were heterogeneous studies carried out at different centers, all showed promising results for AMRI as a screening tool for HCC.…”
Section: Abbreviated Liver Mri (Amri): Suggested Sequences and Diagnomentioning
confidence: 99%
See 2 more Smart Citations
“…and 76.4-87.5%, respectively. 21,23 For EOB-AMRI, the sensitivity and specificity ranged from 80.6-83.7% and 90.6-91.6%, respectively. 19,22 Although these were heterogeneous studies carried out at different centers, all showed promising results for AMRI as a screening tool for HCC.…”
Section: Abbreviated Liver Mri (Amri): Suggested Sequences and Diagnomentioning
confidence: 99%
“…AMRI can be primarily divided into three categories (Table 1): noncontrast AMRI, HBP added to noncontrast AMRI (EOB-AMRI), and dynamic AMRI using an ECCM. [19][20][21][22][23] In prior studies, two to five key sequences were selected for each AMRI protocol to yield a fairly high per-patient sensitivity of 80-89.6% for the diagnosis of HCC. [19][20][21][22][23][24] Particularly, for noncontrast AMRI, the perpatient sensitivity and specificity ranged from 82.9-89.6%…”
Section: Abbreviated Liver Mri (Amri): Suggested Sequences and Diagnomentioning
confidence: 99%
See 1 more Smart Citation
“…A 3-T MR system (verio, Siemens Healthcare, Erlangen, Germany) alongside a phased array coil with 8 channels serving as the receiver coil was employed for MR imaging. Breath-hold half Fourier Acquisition single-shot turbo spin echo, respiratory-triggered fast spin echo T2-weighted image with fat suppression and 3D T1-weighted in-and opposed-phase gradient echo with two-point Dixon reconstruction were obtained as previously described [16].…”
Section: Qualitative and Quantitative Analyses Of Mr Imagingmentioning
confidence: 99%
“…Motivated to provide higher sensitivity than US while avoiding the limitations of CT and conventional MRI, investigators have developed abbreviated MRI (AMRI) protocols that rely on a small number of select sequences specifically tailored for HCC detection [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The rationale is that reduced scanner time decreases costs and complexity, while improving patient comfort, without significantly compromising HCC detection.…”
Section: Introductionmentioning
confidence: 99%